Biospeckle laser technique – A novel non-destructive approach for food quality and safety detection. (March 2020) - Pandiselvam, R.; Mayookha, V.P.; Kothakota, Anjineyulu; Ramesh, S.V.; Thirumdas, Rohit; Juvvi, Praneeth
Abstract: Background: Biospeckle laser technique is an emerging non-destructive, quality detection tool used for the evaluation of biological samples. It is rapid, easy to operate and economical, and assures the quality and safety of the fresh produces. Scope and approach: The biological activity of the materials is altered due to the contamination, damages, maturation, etc. Hence, these factors can be non-destructively analyzed by the biospeckle method combined with the numerical processing techniques. Several qualitative and quantitative methods namely, Fujii, Absolute Value Difference, Inertia Moment, Generalized Difference, etc have been developed for effective biospeckle analysis. Major applications of this tool include identification of bruises, maturation and ripening changes in fruits and vegetables, meat quality detection, seed viability analysis, and detection of fungal colony infection. Key findings and conclusions: Even though the technology has got a wide range of applications, there are some limitations and challenges that hinder its large scale adoption. The impediments such as external noise and interferences have to be addressed to obtain accurate results. There is a need for the development of standardized procedures for conducting the analysis. This review mainly discusses the various applications of biospeckle laser technique as a non-destructive tool in quality and safety analysis, the methods adopted for the evaluation process, the relation between biochemical changes and biospeckle and the various challenges thereof. Highlights: Biospeckle laser technique (BLT) and relevance in agro-products are presented. Utility of BLT in the detection of damage, aging and contamination are discussed. A comprehensive review apprising the applications of BLT in food quality and safety.